2020
DOI: 10.2478/jok-2020-0081
|View full text |Cite
|
Sign up to set email alerts
|

Issues of Railway Traffic Control Devices Availability in the Exploitation Process

Abstract: This article focuses exclusively on the issues of railway traffic control devices availability in traffic management. One of the factors affecting this availability are tests conducted during maintenance or repair works. A review of the literature in the field of test determination methods was conducted. Next, the railway traffic control system was described and the elements influencing availability were defined. Assumptions and an algorithm of the procedure were presented and the method of determining the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Indeed, important deliberations on the traffic situation can be also found in the field of air transport [35][36][37]. The experience of the authors and the negative impacts of checks on device availability identified in the course of test program execution, as described in [38][39][40] is, therefore, a motive for commencing work on developing a method supporting test set determination.…”
mentioning
confidence: 99%
“…Indeed, important deliberations on the traffic situation can be also found in the field of air transport [35][36][37]. The experience of the authors and the negative impacts of checks on device availability identified in the course of test program execution, as described in [38][39][40] is, therefore, a motive for commencing work on developing a method supporting test set determination.…”
mentioning
confidence: 99%